2010
DOI: 10.1177/1941738110377420
|View full text |Cite
|
Sign up to set email alerts
|

Use of Knee Magnetic Resonance Imaging by Primary Care Physicians in Patients Aged 40 Years and Older

Abstract: Background:Criteria are needed for primary care providers such that they can evaluate age-related knee pain in a cost-effective manner. This study examined (1) in what percentage of patients are appropriate radiographic views of the knee ordered before magnetic resonance imaging (MRI) for knee pain, (2) specialists’ retrospective evaluation for appropriate utilization of MRI in knee pain, and (3) in what manner would the MRIs have altered diagnosis and management of knee disorders.Hypothesis:Primary care provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 19 publications
1
35
1
Order By: Relevance
“…When the initial radiographs are noncontributory, a shoulder MRI without contrast or an MR arthrography is appropriate [13]. In a previous retrospective analysis of 100 knee MRIs ordered by primary care physicians, only 44 had corresponding radiographs, and only 12 of 100 would have been ordered by a specialist [20]. Lehnert et al demonstrated in a single-center study that 14% of knee and 37% of shoulder MRIs did not follow the AC, and inappropriate examinations had significantly higher odds of having negative results [21].…”
Section: Discussionmentioning
confidence: 99%
“…When the initial radiographs are noncontributory, a shoulder MRI without contrast or an MR arthrography is appropriate [13]. In a previous retrospective analysis of 100 knee MRIs ordered by primary care physicians, only 44 had corresponding radiographs, and only 12 of 100 would have been ordered by a specialist [20]. Lehnert et al demonstrated in a single-center study that 14% of knee and 37% of shoulder MRIs did not follow the AC, and inappropriate examinations had significantly higher odds of having negative results [21].…”
Section: Discussionmentioning
confidence: 99%
“…The role of imaging in clinical practice for OA diagnosis, management and follow-up has not been clearly defined. Despite this limitation, the increased availability of modern imaging has expanded its use, with possible excesses1 leading to increased costs. A European League Against Rheumatism (EULAR) task force was therefore created to develop evidence-based recommendations on the use of imaging in the management of symptomatic, peripheral joint OA, for clinicians who treat OA in their clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…From 2013, general practitioners (GPs) could request MBS‐subsidized knee MRIs for specific indications (acute knee injury; see MBS item descriptors in Box ). Access to MBS‐funded MRI in primary care may be one driver for the increase in its use, with findings that a large number of MRIs ordered in primary care are considered unnecessary by specialists presented with the same information . An increase in the use of MRI in middle‐aged and older adults with knee pain may also increase inappropriate use of arthroscopy and/or appropriate or inappropriate use of joint replacement.…”
Section: Introductionmentioning
confidence: 99%